A Case of Overlapping Clinical Features of Idiopathic Granulomatous Mastitis, Hidradenitis Suppurativa, and Pyoderma Gangrenosum Successfully Treated with Adalimumab - Vesna Breznik; Pij Bogomir Marko (Case Reports in Dermatology, 2022)
A 36-year-old woman with a 6-month history of painful unilateral mammary nodules and abscesses was initially treated by gynecologists under the diagnosis of idiopathic granulomatous mastitis (IGM). IGM is an entity that has not been described in classical dermatological textbooks and is considered a rare inflammatory breast disease assumingly associated with trauma, infection, or autoimmune system manifestations. In this patient, the lesions were refractory to conventional treatment of IGM comprising of surgical incisions, systemic antibiotics, dexamethasone, and methotrexate. At the initial visit to the dermatology department, a working diagnosis of localized hidradenitis suppurativa (HS) of breast was established, and treatment with systemic doxycycline was initiated. After the diagnostic incisional biopsy, the inflamed nodule deteriorated into a painful ulceration, implying a pathergy phenomenon. Histopathological features were consistent with the granulomatous type of pyoderma gangrenosum (PG). Treatment with systemic methylprednisolone and mycophenolate mofetil was unsuccessful. Subsequently, the patient developed nodules in the inguinal and axillary areas, typical for HS. Finally, adalimumab treatment resulted in the complete resolution of all lesions without relapse even after the biologic therapy was discontinued. Although in this case, IGM was not confirmed histopathologically, we noted several etiopathological and therapeutic similarities between IGM, PG, and HS and summarized them in a unique table. Further observations are needed to ascertain the potential associations among the three entities.